Piercing the Cognitive Fog: The Efficacy of Anemia Screening as a Predictor of Cognitive Decline in Older Adults - Ujianti, Irena; Mustifah, Etty F; Indriyati, Leli Hesti (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2025)
Background: Iron deficiency anemia (IDA) and stunting represent critical public health burdens that disproportionately afflict millions of children globally, particularly in developing nations. While both conditions independently compromise pediatric health and developmental trajectories, emerging evidence suggests a complex, interconnected relationship between the two. Objective: This review aims to investigate the epidemiological and clinical correlation between iron deficiency anemia and the incidence of stunting in children. Furthermore, it seeks to delineate the primary etiological factors driving these conditions and propose targeted intervention strategies to mitigate the prevalence of these concomitant nutritional deficits. Methods: A comprehensive literature review was conducted to synthesize current empirical data regarding the individual impacts of IDA and stunting, with a specific focus on evaluating the synergistic relationship and shared pathways between these two overlapping conditions. Findings: The synthesized literature reveals a significant positive correlation between chronic iron depletion and an elevated risk of stunting. Specifically, the findings demonstrate that the compromised oxygen-carrying capacity inherent in iron deficiency anemia not only impairs cognitive and motor development but also exacerbates chronic linear growth restriction, thereby accelerating the onset of stunting in pediatric populations. Significance: This review bridges a critical gap in pediatric public health by establishing that stunting and iron deficiency anemia are deeply interconnected pathophysiological conditions rather than isolated nutritional deficits. Practically, it provides a crucial, evidence-based framework for healthcare policymakers and clinicians to design integrated, multifaceted nutritional interventions, ultimately shifting the clinical focus from single-nutrient supplementation to comprehensive, early-childhood developmental strategies.